2021
DOI: 10.3389/fcimb.2021.749420
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Induces Apoptosis-Like Cell Death in Leishmania donovani

Abstract: BackgroundVisceral leishmaniasis (VL), caused by the protozoan parasite Leishmania donovani (L. donovani), is the most severe form of leishmaniasis. It is largely responsible for significant morbidity and mortality in tropical and subtropical countries. Currently, available therapeutics have lots of limitations including high-cost, adverse side-effects, painful route of administration, less efficacy, and resistance. Therefore, it is time to search for cheap and effective antileishmanial agents. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
4
12
0
Order By: Relevance
“…promastigotes and provoked the generation of intracellular ROS [ 28 ]. These findings are consistent with other studies which also demonstrated the contribution of ROS production and mitochondrial dysfunction to Leishmania death induced by natural products, such as sesamol, carajurin, apigenin, and quercetin [ 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…promastigotes and provoked the generation of intracellular ROS [ 28 ]. These findings are consistent with other studies which also demonstrated the contribution of ROS production and mitochondrial dysfunction to Leishmania death induced by natural products, such as sesamol, carajurin, apigenin, and quercetin [ 37 , 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…These justify that low cell count at 48 h is due to cell death caused by compounds 9 a and 9 b . Therefore, all these results together clearly indicate that the investigated compounds show antileishmanial activity by generating mitochondrial superoxide radicals [24] …”
Section: Resultssupporting
confidence: 52%
“…Therefore, all these results together clearly indicate that the investigated compounds show antileishmanial activity by generating mitochondrial superoxide radicals. [24]…”
Section: Measurement Of Mitochondrial Superoxide Radical Generationmentioning
confidence: 99%
“…Cells were seeded in six well plates and after the indicated doses treatment for 24 h. Added 10 µM H 2 DCFDA in dark for 45 mins at 37 °C ( Ali et al, 2021 ). Change in Mitochondrial membrane potential was detected using 10 μM Rhodamine 123 solution in media in dark condition for 30 mins at 37 °C.…”
Section: Methodsmentioning
confidence: 99%